A Dynamic Tandem Repeat in Monocotyledons Inferred from a Comparative Analysis of Chloroplast Genomes in Melanthiaceae - Do, Hoang Dang Khoa; Kim, Joo-Hwan (Frontiers in Plant Science, 2017)
Chloroplast genomes (cpDNA) are highly valuable resources for evolutionary studies of angiosperms, since they are highly conserved, are small in size, and play critical roles in plants. Slipped-strand mispairing (SSM) was assumed to be a mechanism for generating repeat units in cpDNA. However, research on the employment of different small repeated sequences through SSM events, which may induce the accumulation of distinct types of repeats within the same region in cpDNA, has not been documented. Here, we sequenced two chloroplast genomes from the endemic species Heloniopsis tubiflora (Korea) and Xerophyllum tenax (USA) to cover the gap between molecular data and explore ‘hot spots’ for genomic events in Melanthiaceae. Comparative analysis of 23 complete cpDNA sequences revealed that there were different stages of deletion in the rps16 region across the Melanthiaceae. Based on the partial or complete loss of rps16 gene in cpDNA, we have firstly reported potential molecular markers for recognizing two sections (Veratrum and Fuscoveratrum) of Veratrum. Melathiaceae exhibits a significant change in the junction between large single copy and inverted repeat regions, ranging from trnH_GUG to a part of rps3. Our results show an accumulation of tandem repeats in the rpl23-ycf2 regions of cpDNAs. Small conserved sequences exist and flank tandem repeats in further observation of this region across most of the examined taxa of Liliales. Therefore, we propose three scenarios in which different small repeated sequences were used during slipped-strand mispairing (SSM) events to generate newly distinct types of repeats. Occasionally, prior to the SSM process, point mutation event and double strand break repair occurred and induced the formation of initial repeat units which are indispensable in the SSM process. SSM may have likely occurred more frequently for short repeats than for long repeat sequences in tribe Parideae (Melanthiaceae, Liliales). Collectively, these findings add new evidence of dynamic results from SSM in chloroplast genomes which can be useful for further evolutionary studies in angiosperms. Additionally, genomics events in cpDNA are potential resources for mining molecular markers in Liliales.